University programs in library and information science in Spain: 2014 data - De-la-Moneda-Corrochano, Mercedes (Anuario ThinkEPI, 2016)
A picture is presented of the state of library and information sciences programs in Spanish universities. Statistics are provided about the number and type of university programs, describing existing institutions, degree levels, student enrolment and instructors.
Keywords: Library and information science; Education; Undergraduate; Master´s degree; Doctorate; Students; Graduates; Teachers; Statistics; Spain